Demanding Innovation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Researchers in ACP countries are facing a growing range of challenges. They are required to respond effectively to the demands of policy makers, private sector investors and donor agencies, farmers and other stakeholders in the agri-food chain. They are b